Contrasting patterns in trophic niche evolution of polymorphic Arctic charr populations in two subarctic Norwegian lakes - Moccetti, Paolo Maria; Siwertsson, Anna; Kjær, Runar; Amundsen, Per-Arne; Præbel, Kim; Tamayo, Ana-Maria Peris; Power, Michael; Knudsen, Rune (Hydrobiologia, 2019)
This is a post-peer-review, pre-copyedit version of an article published in Hydrobiologia . The final authenticated version is available online at https://doi.org/10.1007/s10750-019-3969-9 . Parallelism in trophic niches of polymorphic populations of Arctic charr was investigated in two similar subarctic lakes, Tårnvatn and Skøvatn, in northern Norway. Analysis of eleven microsatellite loci confirmed, respectively, the existence of three and two genetically differentiated morphs. Three methods were used to describe their trophic niches: habitat choice and stomach contents for the recent feeding behaviour, and trophically transmitted parasites and stable isotopes (δ 13 C and δ 15 N) as proxies for the longer term trophic niche differences. The results showed a distinct segregation in trophic resource utilization of the different morphs. Tårnvatn has three morphs: a littoral omnivorous (LO), a small-sized profundal benthivorous (PB), and a large-sized profundal piscivorous (PP). In contrast, a novel Arctic charr morph was discovered in Skøvatn: a small-sized profundal zooplanktivorous-morph (PZ), which when compared to the sympatric LO-morph, had distinct stable isotope values and a contrasting parasite community. A parallelism in habitat choice and external morphology was found among the small-sized, deep-water morphs and between the upper-water, omnivorous LO-morphs in both lakes. There was a no parallel pattern in diet choice between the PB- and the PZ-morphs. These findings show how evolution can produce diverse outcomes, even among systems with apparently similar environmental and ecological conditions.